MiR-146a participates in regulating the progression of periodontitis through the Wnt/β-catenin signaling pathway - Shuixian Gao; Caiqin Mu; Juan Feng; Xiang Sun (PLoS ONE, 2025)
Objectives This study aims to investigate the potential role of miR-146a/Wnt/β-catenin signaling axis in the pathogenesis of periodontitis, using LPS-stimulated hPDLCs as a cell model. Methods Saliva samples were collected from the subjects and qRT-PCR was used to detect the expression of miR-146a and β-catenin in saliva. Clinical parameters, including probing depth (PD) and attachment loss (AL), were measured and their correlation with miR- 146a and β-catenin levels was determined. Cell proliferation capacity was assessed through CCK-8 assay and the production of inflammatory cytokines was evaluated through ELISA kits. Cell cycle distribution was detected by flow cytometry, and gene expression was detected by qRT-PCR and Western blot. Results Our research indicates that compared with the control group, the CP group shows a higher miR-146a expression and a lower β-catenin expression in saliva (P < 0.0001). The expression of miR-146a is positively correlated with AL and PD (P < 0.001), and the expression of β-catenin is negatively correlated with AL and PD (P < 0.001). Inhibiting the expression of miR-146a can promote cell proliferation by regulating cell cycle distribution, reduce the production of inflammatory cytokines, inhibit the expression of p21 and promote the expression of CDK2 and CyclinD1. However, overexpression of miR-146a can result in the opposite effect. In LPS-stimulated hPDLCs, miR-146a expression is up-regulated while β-catenin expression is down-regulated. In addition, overexpression of miR-146a can inhibit β-catenin expression in cells. Simultaneously inhibiting the expression of miR-146a and β-catenin can reverse the effect of inhibiting miR-146a alone on alleviating LPS-induced cell damage. Conclusion miR-146a can inhibit LPS-induced damage to hPDLCs by regulating the Wnt/β-catenin signaling pathway.